A three-phase strategy of bionic drug reservoir scaffold by 3D printing and layer-by-layer modification for chronic relapse management in traumatic osteomyelitis - Yutong Zhang; Tongtong Xu; Tieshu Li; Hening Chen; Guangzhe Xu; Wenxin Hu; Yongting Li; Yue Dong; Zhihui Liu; Bing Han (Materials Today Bio)
We have developed a novel three-phase strategy for osteomyelitis treatment, structured into three distinct phases: the “strong antimicrobial” phase, the “monitoring and osteogenesis” phase and the “bone repair” phase. To implement this staged therapeutic strategy, we engineered a bionic drug reservoir scaffold carrying a dual-drug combination of antimicrobial peptides (AMPs) and simvastatin (SV). The scaffold integrated a bilayer gel drug-carrying structure, based on an induced membrane and combined with a 3D-printed rigid bone graft using a layer-by-layer modification strategy. The mechanical strength of the composite scaffold (73.40 ± 22.44 MPa) is comparable to that of cancellous bone. This scaffold enables controlled, sequential drug release through a spatial structure design and nanoparticle drug-carrying strategy. AMPs are released rapidly, with the release efficiency of 74.90 ± 8.19 % at 14 days (pH = 7.2), thus enabling rapid antimicrobial therapy. Meanwhile, SV is released over a prolonged period, with a release efficiency of 98.98 ± 0.05 % over 40 days in vitro simulations, promoting sustained osteogenesis and facilitating the treatment of intracellular infections by activating macrophage extracellular traps (METs). The antimicrobial, osteogenic and immunomodulatory effects of the scaffolds were verified through in vitro and in vivo experiments. It was demonstrated that composite scaffolds were able to combat the chronic recurrence of osteomyelitis after debridement, by providing rapid sterilization, stimulating METs formation, and supporting osteogenic repair.